2016
DOI: 10.1002/jemt.22672
|View full text |Cite
|
Sign up to set email alerts
|

Light and scanning electron microscopic features of the tongue in cattle egret

Abstract: Adult individuals of both sexes were sacrificed by decapitation and their tongues were teared out in order to be investigated. Cattle egret's tongue is distinguished into the apex, body, and root regions. A shallow median sulcus is apparently noticed on the dorsal surface of the tongue's body only. Histologically, the tongue mucosa is covered with a thick parakeratinized epithelium. The dorsal epithelia of the apex and body are densely packed with exfoliated superficial cells. However, the dorsal surface showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 31 publications
5
12
0
Order By: Relevance
“…(2010a). The shape of the lingual papillary crest has some minor variations; the common shape of the papillary crest takes the transverse appearance (Abumandour & El‐Bakary, 2017a) while in the present study is U‐shaped and agree with that reported by A. Parchami and Fatahian (2011) in pigeon and (Al‐Ahmady Al‐Zahaby, 2016) in cattle egret, but the V‐shaped lingual crest noted by Abumandour, 2018; Abumandour, 2014; Jackowiak & Godynicki, 2005; Jackowiak et al., 2011; Parchami et al. (2010a).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…(2010a). The shape of the lingual papillary crest has some minor variations; the common shape of the papillary crest takes the transverse appearance (Abumandour & El‐Bakary, 2017a) while in the present study is U‐shaped and agree with that reported by A. Parchami and Fatahian (2011) in pigeon and (Al‐Ahmady Al‐Zahaby, 2016) in cattle egret, but the V‐shaped lingual crest noted by Abumandour, 2018; Abumandour, 2014; Jackowiak & Godynicki, 2005; Jackowiak et al., 2011; Parchami et al. (2010a).…”
Section: Discussionsupporting
confidence: 91%
“…The current work referred to the presence of an elevated ovoid‐shaped laryngeal mound containing the glottis in its midline as demonstrated in all avian species (Abumandour, 2018; Abumandour & El‐Bakary, 2017a, 2017b). There was a row of caudally directed papillae observed just caudal to the glottis that was found in most avian species (Abumandour & El‐Bakary, 2017a, 2017b; Al‐Ahmady Al‐Zahaby, 2016); however, this papillary row was absent in southern lapwing (Erdogan & Perez, 2015).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The current work noted the presence of only one transverse papillary row, similar observation observed by Abumandour and El‐Bakary (, , )), but the two transverse papillary row noted by Abumandour (), Abumandour and El‐Bakary (), Parchami et al (), Skieresz‐Szewczyk and Jackowiak (). Also, there are some variations in the appearance of the lingual papillary crest as in the present study, the papillary crest take the transverse appearance, similar to that reported in goose (Iwasaki et al, ) and coot (Abumandour & El‐Bakary, ), while the famous appearance of the papillary crest in the most avian species is the V‐shape as reported by Abumandour (, ), El Bakary (), and Parchami et al () while, it take the W‐shaped in the hoopoe (El‐Bakary, ), but it take a U‐shaped appearance in the cattle egret (Al‐Ahmady Al‐Zahaby, ).…”
Section: Discussionsupporting
confidence: 88%
“…The focused point for the most researchers is the studying the morphological appearance of the tongue and their adaptation with the different feeding styles (Abumandour & El‐Bakary, ; Al‐Ahmady Al‐Zahaby, ; Jackowiak, Andrzejewski, & Godynicki, ; Pasand, Tadjalli, & Mansouri, ). Recently, there are some morphological articles designed to study the morphological characterization of the oropharyngeal cavity (tongue, laryngeal mound, and the palate) and its adaptations with the feeding behavior and the available food materials (Abumandour, ; Abumandour & El‐Bakary, ; Abumandour & Gewaily, ; Kobayashi, Kumakura, Yoshimura, Inatomi, & Asami, ; Santos et al, ).…”
Section: Introductionmentioning
confidence: 99%